Decision-Making Strategy of Hospital Waste Management Using the TOPSIS Method - Dino Rimantho; Gita Azizah Putri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Clinical waste is likely to include disease-causing microorganisms, chemical wastes, and other treatments used to treat different conditions, whether solid or liquid. As a result, clinical wastes have a more significant potential for pathogenicity and toxicity than most other types of waste in all of their forms. This study aims to design a strategic decision model for managing medical waste from hospitals. The method used in this research is the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The data was collected using a questionnaire distributed to three people from various fields: hospital waste management experts, academics, and the environmental service. The results show that the preference for the best hospital waste management strategy is SOP improvement with a weight of 0.6576. Furthermore, the alternative of investing in environmentally friendly technology, 3R campaigns, and outreach to employees and visitors received a weight of about 0.4885, 0.2973, and 0.3393, respectively. This study can be a reference for research related to decision-making strategies and the field of hospital waste management.